2002
DOI: 10.1053/jhep.2002.33715
|View full text |Cite
|
Sign up to set email alerts
|

Detection and identification of bacterial DNA in patients with cirrhosis and culture-negative, nonneutrocytic ascites

Abstract: The current pathogenic theory of spontaneous bacterial peritonitis (SBP) in patients with cirrhosis and ascites suggests that repeated episodes of bacterial translocation (BT) from intestinal lumen to mesenteric lymph nodes followed by systemic seeding are the key steps for the final development of infectious events. However, most of the episodes of systemic bacterial circulation remain undetected. Therefore, we investigated the hypothetical presence of bacteria in blood and/or ascitic fluid (AF) from patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

18
200
5
15

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 271 publications
(238 citation statements)
references
References 27 publications
18
200
5
15
Order By: Relevance
“…It has been shown that 32% of patients with cirrhosis with culture-negative ascites have detectable bacterial DNA in the blood, which may indicate systemic bacterial seeding. 31 An important observation made through ex vivo experiments in this study was the demonstration that the neutrophil functional defect could be transmitted to normal neutrophils incubated with patients' serum. We also showed that the neutrophil dysfunction in the patients was reversible following incubation with normal serum.…”
Section: Discussionmentioning
confidence: 82%
“…It has been shown that 32% of patients with cirrhosis with culture-negative ascites have detectable bacterial DNA in the blood, which may indicate systemic bacterial seeding. 31 An important observation made through ex vivo experiments in this study was the demonstration that the neutrophil functional defect could be transmitted to normal neutrophils incubated with patients' serum. We also showed that the neutrophil dysfunction in the patients was reversible following incubation with normal serum.…”
Section: Discussionmentioning
confidence: 82%
“…The inadequacy of culture-based assays to provide sufficiently rapid, accurate and comprehensive data on which to base clinical decisions has led to the development and use of culture-independent, molecular strategies in an increasing number of clinical contexts. The rationale for taking a culture-independent approach in this study was underpinned by earlier studies that have shown bacterial DNA in fluid from approximately 40% of cirrhosis patients with culture-negative, non-neutrocytic ascites [23,24]. Moreover, the presence of bacterial DNA has recently been shown to be associated with an increased risk of developing SBP [25].…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that roughly 30% of patients with advanced cirrhosis and AF show the simultaneous presence in blood and AF of fragments of bacterial DNA (bactDNA), mostly from the same type of bacteria, 5 and that these fragments may last in blood during variable periods. 6 The identity of the nucleotide sequences detected in a given patient during the study period, together with the fact that bactDNA may disappear and then re-appear in consecutive serum specimens, lead us to consider that the main mechanism promoting the presence of bactDNA in blood was repeated episodes of bacterial movement through the intestinal wall, and not a clearance defect.…”
mentioning
confidence: 99%